2011
DOI: 10.1007/s12033-011-9484-5
|View full text |Cite
|
Sign up to set email alerts
|

High Yield of Human Monoclonal Antibody Produced by Stably Transfected Drosophila Schneider 2 Cells in Perfusion Culture Using Wave Bioreactor

Abstract: Since it was first introduced in late 1990s Wave bioreactor has been used for protein production by mammalian and insect cell lines. However, using Wave bioreactor to produce human monoclonal antibody by stable Drosophila Schneider 2 (S2) cell transfectants has not been reported before. In this study, S2 cells were co-transfected with an inducible vector expressing human monoclonal antibody heavy and light chains, respectively, specific for hemagglutinin (HA) of H5N1 influenza virus. Stable S2 transfectant clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…3A and B). In our study with other S2 clones, we found that using Wave bioreactor stably transfected S2 clones in perfusion culture could grow to 10 8 cells per ml without compromising cell viability (53). Therefore, there is still room to improve HIV-1 VLP production by our stably transfected S2 clones.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…3A and B). In our study with other S2 clones, we found that using Wave bioreactor stably transfected S2 clones in perfusion culture could grow to 10 8 cells per ml without compromising cell viability (53). Therefore, there is still room to improve HIV-1 VLP production by our stably transfected S2 clones.…”
Section: Discussionmentioning
confidence: 68%
“…To test the antigenicity of HIV-1 envelope glycoproteins produced by stably transfected S2 clones, we performed three sets of experiments with a panel of broadly neutralizing antibodies-2G12, b12, VRC01, PG16, and 4E10 (6, 7, 52, 55, 60, 63)-as well as the control antibody 100F4 antibody (53). The antige- nicity results of HIV-1 envelope glycoproteins are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The D265A mutant was generated using specific primers and the QuikChange site-directed mutagenesis kit II (Agilent Technologies) and validated by direct sequencing. The expression vectors containing genes encoding the chimeric 100F4 or 65C6 heavy chains along with the expression vectors containing genes encoding the 100F4 or 65C6 light chain, respectively, were cotransfected into Drosophila S2 cells, and stably transfected S2 cell clones were selected as described before (47). The cAbs 65C6/IgG2a, 65C6/D265A, 100F4/IgG2a, and 100F4/D265A were produced by the stably transfected Drosophila S2 clones and purified by affinity chromatography using protein A agarose (Pierce; Thermo Fisher Scientific) and quantified by bicinchoninic acid (BCA) protein assay kit (Thermo Fisher Scientific) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%